2022
DOI: 10.1039/d2sm00566b
|View full text |Cite
|
Sign up to set email alerts
|

The fate of liquid crystal topological defects on chemically patterned surfaces during phase transitions

Abstract: Controlling topological defects in liquid crystals (LCs) is an essential element in the development of areas such as directed self-assembly and micropatterning materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Liquid crystal (LC) materials have been widely studied as candidates for fabricating nano/microstructures because their morphology is easily controlled under surface treatment, spatial confinement, and external field applications due to the anisotropic characteristics of the LC phase. The resulting LC structures can be used in various optical, lithographic, and particle-manipulating tools. ,, However, the LC material has poor mechanical properties since it is fluidic, limiting its further application and requiring unique equipment to observe its internal structure. , In this regard, reactive mesogen (RM), a liquid crystalline monomer with polymerizable end groups, has been receiving much attention along with its diverse functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystal (LC) materials have been widely studied as candidates for fabricating nano/microstructures because their morphology is easily controlled under surface treatment, spatial confinement, and external field applications due to the anisotropic characteristics of the LC phase. The resulting LC structures can be used in various optical, lithographic, and particle-manipulating tools. ,, However, the LC material has poor mechanical properties since it is fluidic, limiting its further application and requiring unique equipment to observe its internal structure. , In this regard, reactive mesogen (RM), a liquid crystalline monomer with polymerizable end groups, has been receiving much attention along with its diverse functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47] Furthermore, topologically non-trivial colloidal particles can be made and subimmersed in liquid crystals to induce various types of topological defects, including links, knots and networks of disclinations. [48][49][50] These methodological advancements have also opened up opportunities for studying the roles of preprogrammed topological defects in phase transitions such as nematic-isotropic 51,52 and nematic-to-smectic transitions. 53 It was found that even without topological defects, the N-I transition temperature could be altered by spatially variant director fields.…”
Section: Introductionmentioning
confidence: 99%